Challenges in Economic Policy Formation with Digital Market Disruptions: With Reference to India - Sharma, Prachee; Dey, Sujit; Krishnan, Pragati; Tiwari, Muklesh Kumar; Shridhar, Sheela; Shrivastava, Reshma; Mertiya, Teena; Bohre, Padma; Siddiqui, Imran Nadeem; Dewangan, Jay Kumar (Journal of Cultural Analysis and Social Change, 2026)
India's digital economy is now among the most vibrant globally, adding a projected USD 500 billion to GDP in 2023, or 11% of output. The explosive expansion of fintech, e-commerce, and the gig economy holds opportunities but also challenges of regulation for policymakers. This paper combines quantitative analysis with qualitative examination to analyze the economic effects of digital market disruption. Based on secondary data from MeitY, RBI, World Bank, and NITI Aayog (2015–2024), the analysis reports strong positive correlations of digital adoption and GDP growth (r = 0.82), diversification of employment, and financial inclusion. Nevertheless, taxation, data privacy, and labour protection issues remain. The paper suggests evidence-based policies balancing innovation with equity to ensure long-term digital advancement.